Geographical distribution and risk assessment of dichlorodiphenyltrichloroethane and its metabolites in Perna viridis mussels from the northern coast of the South China Sea. (February 2020) - Sun, Runxia; Yu, Juan; Liao, Yuhao; Chen, Jiemin; Wu, Zetao; Mai, Bixian
Abstract: Mussels ( Perna viridis ) were collected from the northern coast of the South China Sea (NSCS) to investigate the geographical distribution and potential risk of dichlorodiphenyltrichloroethane and its metabolites (DDTs). DDTs had concentrations that ranged from 248 ng/g to 4650 ng/g lipid weight (lw), with an average of 807 ± 932 ng/ng lw. A comparison of the levels of DDTs in mussels indicated that the NSCS is still one of the most polluted areas in the world, although a decreasing trend was observed. DDT metabolites were predominant in all samples, suggesting that historical residue was the main source of DDT pollution. However, there were new inputs of DDTs which likely associated with antifouling paints. The human health risk assessment revealed that the current concentrations of DDTs in mussels might pose little health risk for the consumers. Highlights: Mussels were used as the bioindicator of monitoring DDTs. DDTs were investigated in the northern coast of the South China Sea. History residual DDTs remain playing an important role. Mussel consumption might pose little health risks to humans.